Exogenous strigolactones modulate antioxidant metabolism via CsD27 to enhance drought tolerance in tea plants - Shen, Jingyue; Tong, Manni; Yuan, Qingyun; Long, Lizhi; Shi, Yuanzhi (Frontiers in Plant Science, 2025)
Drought stress adversely affects the growth, yield, and quality of tea plants (Camellia sinensis L.). Although strigolactones (SLs) are known to mediate drought adaptation in plants, their regulatory mechanisms in tea plants remain elusive. In this study, we demonstrated that exogenous SL application alleviated drought-induced symptoms by photosynthetic adaptation and mitigating the damage of cell membrane. Moreover, exogenous SL enhanced antioxidant response through regulating catechins metabolism in drought-sensitive cv. ‘Huangjinya’. Notably, we identified CsD27 as a key SL-biosynthetic gene, whose expression level was negatively correlated with malondialdehyde (MDA), mechanistically linking its function in drought tolerance in tea plants. Overexpression of CsD27 enhanced the drought tolerance of transgenic Arabidopsis with decreased MDA content and increased survival rate under drought stress. These findings elucidate a dual SL-mediated mechanism that simultaneously enhances stress tolerance and preserves tea quality, which provide a potential target for molecular breeding in perennial crops.